2014
DOI: 10.1186/1471-2229-14-66
|View full text |Cite
|
Sign up to set email alerts
|

QTL architecture of reproductive fitness characters in Brassica rapa

Abstract: BackgroundReproductive output is critical to both agronomists seeking to increase seed yield and to evolutionary biologists interested in understanding natural selection. We examine the genetic architecture of diverse reproductive fitness traits in recombinant inbred lines (RILs) developed from a crop (seed oil) × wild-like (rapid cycling) genotype of Brassica rapa in field and greenhouse environments.ResultsSeveral fitness traits showed strong correlations and QTL-colocalization across environments (days to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Li et al, 2014). Fruit length is considered to be a suitable trait to select for in B. napus (Samizadeh et al, 2010) because high heritability is observed for this trait, which is less sensitive to GxE than, for example, the total number of fruits per plant (Chay and Thurling, 1989;Dechaine et al, 2014). In this experiment, high heritability was also observed for silique length (Table 3).…”
Section: Homology Of Heat Stress Responses Between Speciessupporting
confidence: 51%
See 1 more Smart Citation
“…Li et al, 2014). Fruit length is considered to be a suitable trait to select for in B. napus (Samizadeh et al, 2010) because high heritability is observed for this trait, which is less sensitive to GxE than, for example, the total number of fruits per plant (Chay and Thurling, 1989;Dechaine et al, 2014). In this experiment, high heritability was also observed for silique length (Table 3).…”
Section: Homology Of Heat Stress Responses Between Speciessupporting
confidence: 51%
“…Total yield is determined by several plant traits, such as total fruits per plant, seed weight, seeds per fruit, and fruit length. The last three are correlated and many coinciding QTLs have been reported (Alonso-Blanco et al, 1999;Dechaine et al, 2014;N. Li et al, 2014).…”
Section: Homology Of Heat Stress Responses Between Speciesmentioning
confidence: 99%
“…Individual replicates of each RIL were sown into peat pots filled with field soil and topped with 1 cm LP5 potting soil (Sun Gro Horticulture, Agawam, MA). Seeds were planted in the first week of June 2011, and pots were transplanted to the field 2.5 wk later following established protocols (Dechaine et al 2014). One biological replicate of each genotype was planted into each of five fully randomized blocks.…”
Section: Plant Growth and Tissue Collectionmentioning
confidence: 99%
“…For this study, we utilized an existing RIL population of B. rapa that has been used extensively for QTL mapping of physiological, developmental, and evolutionarily important traits [BraIRRi; Baker et al 2015;Brock et al 2010;Dechaine et al 2007Dechaine et al , 2014Edwards et al 2011;Iniguez-Luy et al 2009;Lou et al 2011Lou et al , 2012. Recently, we completed deep RNA-Seq of the parents of the BraIRRi population, providing a large SNP set and improved gene annotation information (Devisetty et al 2014).…”
mentioning
confidence: 99%
“…QTL co-localization has been reported for traits that are strongly correlated (Dechaine et al , 2014). Many clustered, putatively pleiotropic QTL have been found that affect various life history and fitness characters, especially those that are related to yield, in rice, wheat, pea and rapeseed (Burstin et al , 2007; Quarrie et al , 2006; Shi et al , 2009; Xue et al , 2008).…”
Section: Introductionmentioning
confidence: 99%